A Study Falling Particles In Various Types Of Fluids With Different Viscosity - Musa, Shah Mudzaffar (Universiti Sains Malaysia, 2001)
In many kind of process, especially technical separation, there is always been a motion of particles in certain medium. The transferable of particles from one place to another make it easier for some system or process to meet its target. The medium can be anything that is like liquid or gaseous, weather it is in stationary or in motion. For example, the disposable ashes form gas medium, transformation of solid from wasted air, and also the recycle process to gain back the acidic fluid form chemical plantation. Overall, there are many literatures that have been published for public knowledge, and there a lot of knowledge that can be gained from these journals about motion of fluid with a stationary immersed particle in it. All of the parameters and variables that related to this thesis are considerably useful to generate new ideas and new models of equations. The purpose of it is to get the variations of velocity and acceleration relatively with time and distance deviation. In this thesis, a mathematical model was develop for a spherical particle falling in various type of liquid with different value of viscosity i.e. viscosity of acid acetic, 1  0.001095 Ns m2, alcohol, ethyl,  2  0.00192 Ns m-2, alcohol propyl.   0.00164 Ns m-2, kerosene,   0.00153 Ns m-2, mercury,   0.001375 Ns m-2, and turpentine,   0.001155 Ns m-2. The mathematical model was solved using the boundary conditions, the sum of all forces that acted on the spherical particle and some assumption has been made to solve the equations model. An expression was obtained, from which the velocity versus time was deducted for transient and steady state conditions. This result is a simulation of a fall particle in a heated fluid, but in order to get the mathematical solutions, the simulations was change to a falling particle in various type of fluid with different value of viscosity. The results that were obtained here maybe not as same as the experimental value if it was conducted, but think of how powerful a mathematical model is when it is applied to gain the result of an experiment that hasn’t been done yet.